Characteristics and outcomes of normal-flow low-gradient aortic stenosis patients compared to high-gradient aortic stenosis patients undergoing TAVI. (3rd October 2022) - Steffen, J; Andreae, D; Haum, M; Fischer, J; Doldi, P; Peterss, S; Hausleiter, J; Rizas, K; Braun, D; Orban, M; Nabauer, M; Massberg, S; et al.
Abstract: Background: Guidelines recommend aortic valve replacement for aortic stenosis (AS) depending on mean pressure gradients (dPmean) and flow status. It is indicated when dPmean is ≥40 mmHg (high-gradient, HG) or when patients have low-flow low-gradient AS. Normal-flow (stroke volume index, SVi >35 ml/m 2 ) low-gradient (dPmean <40 mmHg) (NFLG) AS is subject of scientific debate and severe AS is considered unlikely in current European guidelines. Purpose: We hypothesized that NFLG patients are heterogenous, containing a subgroup similar to HG patients in terms of characteristics and outcomes. The purpose of this study was to identify and assess this subgroup by dividing NFLG patients by dPmean. Methods: All patients undergoing transcatheter aortic valve implantation (TAVI) at our centre between 2013 and 2019 were analysed and categorised into groups according to dPmean, left-ventricular ejection fraction, and SVi. Among 2, 326 patients analysed, 386 patients fulfilled criteria for NFLG AS (dPmean <40 mmHg, LV-EF ≥50%, SVi >35 ml/m 2 ). They were further subdivided into two groups according to the median dPmean and were compared to 956 HG AS patients (dPmean ≥40 mmHg). Groups were compared for baseline characteristics, mortality, and outcomes according to Valve Academic Research Consortium (VARC) 3 definitions. Results: Median dPmean was 33 mmHg in NFLG patients. Accordingly, they were split into two groups, with 204 patients above (higher gradient NFLG) and 182 patients below (lower gradient NFLG) this value. Characteristics of lower gradient NFLG patients differed from HG patients in many aspects while they were similar between higher gradient NFLG and HG patients. This was underscored by higher Society of Thoracic Surgeons (STS) scores in lower gradient NFLG compared to the other two groups (Table). Procedural and short-term clinical complications were similar between groups. The VARC-3 composite endpoint of technical failure occurred in 42 HG (4.4%), 12 higher gradient NFLG (5.9%), and 5 lower gradient NFLG patients (2.7%, p=0.32). The rates of the VARC-3 composite endpoint of device failure at 30 days were 108 patients (11.3%), 21 patients (10.3%), and 17 patients (9.3%), respectively (p=0.71). At follow-up, symptoms of patients from all three groups improved equally by at least one New York Heart Association class (p=0.47). Hazard ratio (HR) for 3-year mortality for all NFLG patients vs. HG patients was 1.4 [95% confidence interval, CI, 1.1–1.8]. Estimated 3-year all-cause mortality was significantly higher in lower gradient NFLG compared to HG patients, whereas mortality rate of higher gradient NFLG was similar to HG (Figure). Conclusions: The data show that a large subgroup of NFLG patients has characteristics similar to those of HG patients, with similar clinical and procedural outcomes and comparable mortality rates. If severe AS was identified as the main clinical problem in this subgroup, aortic valve replacement can be justified. Funding Acknowledgement: Type of funding sources: None.